Comprehensive Transcriptome Analysis of Six Catfish Species from an Altitude Gradient Reveals Adaptive Evolution in Tibetan Fishes. Issue 1 (1st January 2016) - Ma, Xiuhui; Dai, Wei; Kang, Jingliang; Yang, Liandong; He, Shunping
Abstract: Glyptosternoid fishes (Siluriformes), one of the three broad fish lineages (the two other are schizothoracines and Triplophysa ), have a limited distribution in the rivers in the Tibetan Plateau and peripheral regions. To investigate the genetic mechanisms underlying adaptation to the Tibetan Plateau in several fish species from gradient altitudes, a total of 20, 659, 183–37, 166, 756 sequence reads from six species of catfish were generated by Illumina sequencing, resulting in six assemblies. Analysis of the 1, 656 orthologs among the six assembled catfish unigene sets provided consistent evidence for genome-wide accelerated evolution in the three glyptosternoid lineages living at high altitudes. A large number of genes refer to functional categories related to hypoxia and energy metabolism exhibited rapid evolution in the glyptosternoid lineages relative to yellowhead catfish living in plains areas. Genes showing signatures of rapid evolution and positive selection in the glyptosternoid lineages were also enriched in functions associated with energy metabolism and hypoxia. Our analyses provide novel insights into highland adaptation in fishes and can serve as a foundation for future studies aiming to identify candidate genes underlying the genetic basis of adaptation in Tibetan fishes.